PENINGKATAN PRODUKSI INDUSTRI RUMAH TANGGA JAJE BEGINA DI DESA TEGAL LINGGAH KABUPATEN KARANGASEM - I Ketut Putu Suniantara; Gede Suwardika; I Made Rudita; Kadek Masakazu; I Gede Darsana; I Gede Suardika; I Made Ari Santosa; I Made Agus Wirahadi Putra; I Gede Nika Wirawan (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
The partner in this community partnership program activity is Mrs. Ni Nengah Resti whose address is in Tegallinggah Village, Karangasem District. Jaje begina production is produced using sufficient and simple equipment, both in processing and in the packaging process. Marketing is carried out conventionally by partners by leaving products in nearby stalls and selling them to the market. Another obstacle faced by partners in the packaging process is still using staples without labels. The solutions provided in this service activity are based on the principles of intensification, extensification and rationalization in three activity methods of awareness, capacity building and mentoring. The aim of this community service is how to increase the quantity and quality of products from partners. The results of the service show that partners are able to increase the quantity and quality of products, where the time needed to produce such snacks is shorter than before. Products produced by partners already have the label "jaje begina me' resti" with marketing using the social media fan page Facebook. The partner response was very satisfying with a percentage of 72,14%.